COHELLP: collaborative randomized controlled trial on corticosteroids in HELLP syndrome - Katz, Leila; Amorim, Melania; Souza, João P; Haddad, Samira M; Cecatti, José G (Reproductive health, 2013)
Background Hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome is one of the most severe forms of preeclampsia and aggravates both maternal and perinatal prognosis. The systematic review available in Cochrane Library compared corticosteroid (dexamethasone, betamethasone, or prednisolone) given during pregnancy, just after delivery or in the postnatal period, or both before and after birth, with placebo or no treatment. Those receiving steroids showed significantly greater improvement in platelet counts which was greater for those receiving dexamethasone than those receiving betamethasone. There was no clear evidence of any effect of corticosteroids on substantive clinical outcomes. These benefits appear to be greater in Class I HELLP syndrome. Objectives To determine the effectiveness of dexamethasone for accelerating postpartum recovery in patients with Class I HELLP syndrome in a multicenter randomized controlled trial. Methods/Design The study is a triple blind randomized controlled trial including women with class I HELLP syndrome, and exclusion criteria were dexamethasone use in the last 15 days before diagnosis of HELLP syndrome; chronic use of corticosteroids; chronic diseases that alter laboratory parameters of HELLP Syndrome, such as chronic liver disease or purpura, patients unable to consent (coma or critical clinical condition) and without accompanying persons that may consent to study participation. Eligible patients will be invited to participate and those who agree will be included in the study and receive placebo or dexamethasone according to a random list of numbers and subjects will receive the study medication every 12 hours for two days. During the study the women will be subject to strict control of blood pressure and urine output. Laboratory tests will be performed at regular intervals during treatment and 24 hours and 48 hours after its suspension. If worsening of clinical or laboratory variables is observed, a rescue scheme of dexamethasone will be administrated. This proposal has already obtained approval of the local Institutional Review Board of the coordinating center (IMIP, Recife, Brazil), all other participating centers and of the National Council for Ethics in Research (CONEP) of the Brazilian Ministry of Health. Trial Registration Clinical Trials Register under the number NCT00711841 .